Analisis Pengaruh Kemiskinan, Pengangguran, Dan Pertumbuhan Ekonomi Terhadap Kualitas Pembangunan Manusia - Indira Hasmarini, Maulidiya; Parendra Surya, Annisa (Fakultas Ekonomi Universitas Gresik, 2023)
Human development is a process of expanding choices for people, especially in accessing development outcomes such as income, health, and education. One of the benchmarks can be seen from the Human Development Index. The purpose of this study was to determine the effect of poverty, unemployment and economic growth on the Human Development Index (IPM) in East Java Province in 2015-2020. The analytical tool used is panel data with a combination of time series and cross section. The results of the effect validity test (t test) on the econometric model show that the number of poor people has an effect on the Human Development Index in Regencies/Cities in East Java (IPM). This proves that the results of this study based on the analysis show that the poverty level variable has a significant effect on HDI and is statistically significant, having a regression coefficient of 0.081158. The results of the influence validity test (t test) on the econometric model show that the unemployment rate has an influence on the Human Development Index in Regencies/Cities in East Java (IPM). This proves that the results of this study based on the analysis show that the unemployment rate variable has a significant effect on HDI and is statistically significant, having a regression coefficient of 0.107681. The results of the influence validity test (t test) on the econometric model show that Economic Growth has an influence on the Human Development Index in Regencies/Cities in East Java (IPM). This proves that the results of this study are in accordance with the initial hypothesis and these results are in accordance with the research conducted based on the analysis showing that the economic growth rate variable has a significant effect on HDI and is statistically significant, having a regression coefficient of 0.146907.